A CONSTRUÇÃO EM CROSS LAMINATED TIMBER NO BRASIL - Oliveira, Gabriela Lotufo; Oliveira, Fabiana Lopes de (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Cross Laminated Timber (CLT) panels are a relatively new building component. The panels have first been developed in Europe during the 1990-decade and their production in Brazil started in 2012. CLT components are structural solid wood panels that can be used as wall, floors, ceilings, beams or columns, among other structural elements of any kind of buildings, such as residential and commercial buildings, schools or hospitals. Most of the CLT buildings constructed in Brazil from 2012 until 2017 are single-family houses. Therefore, taking in account that the component is not widely known in the country, this article aims to analyze those residential buildings in order to contextualize CLT construction in Brazil. To do so, the residences were catalogued and analyzed in terms of the construction technique and details adopted. Also, one house was chosen as a case study. The results indicate the importance of considering the panels characteristics in order to prevent building pathologies.